Cybersecurity provision and online services access and usage - Maria Lurdes Martins (International Telecommunications Society (ITS), 2023)
Understanding cybersecurity role in digital and online services expansion is of interest to firms, academic research, as well as public policies aiming at supporting economic development. Thus, this paper aims to assess whether improved cyber security can affect the trust needed by online services markets participants to reduce observed international differences in several dimensions of the digital economy and society. Furthermore, we explore the extent to which our results are especially relevant for countries in early stages of their mobile communications networks. We combine data, at the national level, from the 2017 SIR regional reports with broader information data from the ITU cybersecurity index for the period 2014-2021 to obtain empirical evidence on the relationship between cyber security and digital and online services expansion at the country level. We find a negative relationship between citizens, government and businesses' overall digital adoption and cyber insecurity at the country level. Furthermore, we extend this result to the relationship between cybersecurity and content access and online services diffusion. The results confirm that, in addition to other socioeconomic variables, cybersecurity is an important factor explaining the observed worldwide disparities in the studied dimensions of content access and online services access and usage. We also ascertain that cybersecurity role in content access and online services expansion may be less important to understand social media penetration in economies with lower mobile communications connectivity in comparison with more developed ones. By contrast, there seems to exist a similar negative cyber insecurity effect in apps development and availability for all countries regardless of their mobile connectivity development level.
Keywords: 330; cybersecurity; digital divide; socioeconomic inequalities